Pengaruh Online Booking & Offline Booking Terhadap Peningkatan Occupancy pada Marc Hotel Passer Baroe - Agata Claudia Mawarni; Eko Harry Susanto (Jurnal Manajemen Bisnis dan Kewirausahaan, 2020)
ifestyle is a piece of human life nowadays. People do many things to express their desire, and also to try new experience. One of such things is traveling. The technology growth has enabled simplicity and ease of access to all necessity, such as transportation, equipment, and more importantly, lodgings such as hotels and inns.Based on the improvement of facility, people now can easily book hotels using only a few gestures. Online travel agency industry is growing, and partnership between hotels and the agency is getting thicker. Booking via apps or site only takes a few seconds to do, yet some people still prefer booking directly through phone or reception desk staff. Based on that thought, a goal is set to look deeper on both online and offline booking effects on hotel’s occupancy rate.The data used for making this research is from Marc Hotel Passer Baroe. The data was taken from the company monthly statistics report from January to October 2019. The conclusion was that the online booking partially affects the occupancy rate negatively, and offline booking partially affects the positively. Both variables simultaneously affect the positively. Thus, the company should focus on better promotion on offline booking programs, encouraging patron to book directly to them instead of 3rd party.